Analisis Kinerja Pegawai terhadap Kepuasan Pelanggan dalam Aplikasi PLN Mobile di PT PLN (Persero) Unit Induk Wilayah Maluku dan Maluku Utara - Buton, Wulan Aulia; Mohamad Arsad Rahawarin; Julia Theresia Patty (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
This study analyzes the impact of employee performance on customer satisfaction in using the PLN Mobile application at PT PLN (Persero) Unit Induk Wilayah Maluku and Maluku Utara. The study employs simple linear regression analysis, utilizing t-tests and F-tests to assess the significance of the relationship between variables. The findings reveal that employee performance has a positive and significant effect on customer satisfaction, with a regression coefficient of 0.787 and a significance value of < 0.001. The F-test results indicate that the regression model is valid and effectively explains variations in customer satisfaction, with an F-value of 1834.299, significantly exceeding the critical F-table value. Additionally, the high coefficient of determination (R²) suggests that most variations in customer satisfaction can be explained by employee performance. This study confirms that optimizing employee performance is a key factor in improving customer satisfaction, particularly in digital services such as PLN Mobile. Therefore, PT PLN (Persero) must enhance employee competence and service quality to support digital transformation and meet customer expectations.